PRODUKSI MIKOINSEKTISIDA DARI PROPAGUL KAPANG Beauveria Bassiana - Wahyudi, Priyo (LPPM Universitas Terbuka, 2008)
Fungal insecticide or well known as mycoinsecticide is produced from propagules of entomopaghogenous fungi. It is a common knowledge that fungi can kill insects, individually or in epizootics, and methods for isolation and exploration of fungi are well known. Despite these facts, production of commercial preparations with fungi came very late. There is only one commercial product, which is produced on a large scale for several years. Beauveria bassiana is one of entomopathogenic fungus that has been used for biocontrol of many insects of crops. In this article we assess production of mycoinsecticide Beauveria bassiana through all stages of their handling, such as isolation, strain selection and optimation of production procedures both liquid and solid state fermentation. The result showed that the best way to produce mycoinsecticide in a large scale production was solid state fermentation using rice-base medium including cooked-rice and rice flour. The best incubation can be taken place in room temperature for 7 days.